Reimagining Asceticism in Our Times: The Case of New Skete - Solovieva, Olga (The international journal of religion and spirituality in society, 2012)
Drawing on my fieldwork at the Communities of New Skete and research in the history of Christian monastic tradition, this paper presents a case study in the contemporary transformations of asceticism. Founded in 1966 by a group of ex-Franciscan monks, New Skete was a product of, and an active participant in, the religious experiments and monastic renewals of the sixties. Today New Skete is a well-established community that enjoys a growing (if at times, controversial) reputation within and beyond the American Orthodox Church. Yet, the spirit of experimentation in search for a way of life that is genuinely ascetic and contemplative yet open to the needs of contemporary society continues to animate its approach to monasticism. My paper will touch upon several aspects of this ongoing effort, such as New Skete’s innovative form of communal life (a male/female monastery including both celibate and married monastics), integration of the contemplative life and action (as exemplified by New Skete’s nationally famous dog-raising program), and the community’s relationship with the wider society. My particular interest is in the ways in which New Skete’s ascetic vision and praxis challenge the dichotomy between the "world" and the "desert," the monastery and society, traditional monastic "askesis" and the spiritual practice in ordinary life.